Developing and fully developed turbulent flow through annuli - Singh R.P.; Nigam K.K.; Mishra P. (My University, 2025)
Turbulent flow velocity profiles for the inner and outer flow regions of annuli are proposed. Theoretical expressions for friction factors and entrance region pressure drops are developed and are further extended to the limiting cases of pipes and parallel plates. Experimental data are found to be in good agreement with theoretical results. © 1980, The Society of Chemical Engineers, Japan. All rights reserved.